Communicating pregnancy complication: a discourse analysis of an online support group - Vidyarini, Titi Nur (Faculty of Communications Science, Dr. Soetomo University, 2020)
The increase use of internet open up a broad spectrum of usage. Among those are the use of sharing platform such as Instagram and facebook for particular communities. Support groups are essential part of health treatment and recovery, in this case for pregnancy condition. One can try to find solace and information through online support group. Online support group enable people from around the globe to communicate, discuss and encourage others with similar condition. This article delves the question of how women use internet-based health support group. The researcher conduct qualitative discourse analysis on an online pregnancy support group and various literatures which explores the use of internet-based support group. The findings show that women use online support group because they found lack of support offline, they need information and emotional support regarding their pregnancy loss and the recovery process, the role of medical expert and the spouses are perceived differently.